2017
DOI: 10.5688/ajpe81358
|View full text |Cite
|
Sign up to set email alerts
|

Point/Counterpoint: Are Outstanding Leaders Born or Made?

Abstract: The question of whether outstanding leaders are born or made has been debated for years. There are numerous examples of historical figures that came naturally to leadership, while others developed their leadership skills through tenacity and experience. To understand leadership, both nature (the genetic component) and nurture (the environmental influences) must be considered. This article represents the work of two Academic Leadership Fellows Program groups who debated each position at the 2016 American Associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Leadership requires a wide variety of skills. 37,38 As a CEO dean, it is impossible to be an expert in all areas of pharmaceutical science, practice, management, leadership, budgeting, fundraising, strategic planning, and human resources. An analogy might be drawn from the arena of sports coaching.…”
Section: Discussionmentioning
confidence: 99%
“…Leadership requires a wide variety of skills. 37,38 As a CEO dean, it is impossible to be an expert in all areas of pharmaceutical science, practice, management, leadership, budgeting, fundraising, strategic planning, and human resources. An analogy might be drawn from the arena of sports coaching.…”
Section: Discussionmentioning
confidence: 99%
“…The question of whether these strong females are nurtured in their leadership roles or if these women have advanced in their professions because of their strong qualities is raised by the distinguished characteristics shared by these women. Previous research has shown conflicting results regarding whether a person develops leadership skills through time or is born with them [36,37]. Female leaders stand out in environments where men predominate because they see themselves as powerful individuals and leaders.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Many past cohorts have published guidance documents or statement papers related to their debate topics. [1][2][3] The two teams involved in our debate topic have worked together on a manuscript, generating more networking and a great opportunity to better know fellows outside of their teams.…”
Section: A J P Ementioning
confidence: 99%